STABILITY OF SHARIAH-COMPLIANT STOCKS IN INDONESIA, MALAYSIA, AND GCC: THE ROLES OF MONETARY AND FISCAL POLICIES AND CONTAGION - Ooi Kok Loang (Journal of Islamic Monetary Economics and Finance, 2024)
This study examines the roles of monetary and fiscal policies and contagion in the market stability of Indonesia, Malaysia, and the Gulf Cooperation Council countries during the pandemic and post-pandemic periods from 2020 to 2023. We find that fiscal policy measures, such as reserve requirements and the government expenditure-to-GDP ratio significantly increase the market volatility during the pandemic. As for monetary policy tools, while they had limited effectiveness during the pandemic, they regained significance in stabilizing the markets post-pandemic.  We also find that the patterns of market contagion patterns tend to vary across countries, with Qatar and Bahrain showing changing levels of contagion while Saudi Arabia, UAE, Kuwait, and Oman consistently displaying moderate to high contagion, the results that are in line with the adage, "when the U.S. sneezes, the global economy has a cold". The study's implications for managers and policymakers in Muslim-majority countries include robust risk management and contingency planning due to higher market contagion in economically integrated economies. Additionally, the limited impact of conventional monetary policies during the pandemic highlights the need to explore alternative approaches to enhance market stability during economic downturns.